An Evaluation of TOEFL Benchmark Policy as an Exit Requirement for Undergraduate Students - Rahma, Endah Anisa; Syafitri, Rina; Syahputri, Veni Nella; Parlindungan, Firman (Association of Language Teachers in Southeast Asia (ALTSA), 2021)
This study investigated the TOEFL benchmark policy as an exit requirement for Universitas Teuku Umar students. The research method used was survey design hereby the data from the questionnaire and students' TOEFL score were collected. Under the policy, the students have to pass the standard passing score of TOEFL to graduate. 100 non-English major students from Universitas Teuku Umar participated in this study. The results of the study revealed that the participants gave more positive responses than negative ones. The extend of approval for this policy seemed more related to their abilities, awareness of the importance of learning English, and motivation to learn English. The result from TOEFL scores taken from 2018-2019 found that as many as 58% of students failed to obtain minimum criteria (Ã‹Æ’ 400) while only 42% of them reached 400 or above. It indicates that Universitas Teuku Umar students are not ready yet to face this policy.Ã‚Â On the other hand, based on the questionnaire result, most students agreed with the implementation of TOEFL as an exit requirement, however, a minimum passing score should be evaluated and a set of students' needs under the policy should be facilitated.